Impact of High-Deductible Health Plans on Breast Reconstruction: Considerations for Financial Toxicity. Issue 2 (8th November 2022) - Shamsunder, Meghana G.; Sheckter, Clifford C.; Sheinin, Avraham; Rubin, David; Parikh, Rajiv P.; Rose, John; Momoh, Adeyiza O.; Offodile, Anaeze C.; Matros, Evan
Abstract : Background: High-deductible health plans (HDHPs) are used within the United States to curb unnecessary health care spending; however, the resulting increased out-of-pocket (OOP) costs may be associated with financial toxicity. The aim was to assess the impact of HDHPs on use and seasonality of mastectomy and breast reconstruction procedures. The hypothesis is that the high OOP costs of HDHPs will lead to decreased overall service use and greater fourth-quarter use after the deductible has been met. Methods: MarketScan was queried from 2014 to 2017 for episodes of mastectomy, breast reconstruction (immediate and delayed), breast revision, and reduction. Only patients continuously enrolled for the full calendar year after the index operation were included. HDHPs and low-deductible health plans (LDHPs) were compared based on OOP cost sharing. Outcomes included surgery use rates, seasonality of operations, and median/mean OOP costs. Results: Annual mastectomy and breast reconstruction use rates varied little between LDHPs and HDHPs. Mastectomies, delayed breast reconstruction, and elective breast procedures ( P < 0.001) all showed significant increases in fourth-quarter use, whereas immediate breast reconstruction did not. Regardless of timing and reconstruction method, HDHPs had significantly greater median OOP costs compared to LDHPs (all P < 0.001). Conclusions: Mastectomy and breast reconstruction rates did not differ between LDHPs and HDHPs, but seasonality for all breast procedures was measured with the exception of immediate breast reconstruction, suggesting that women are rational economic actors. Regardless of service timing and reconstruction modality, HDHP patients had greater OOP costs compared to LDHP patients, which serves as a good starting point for provider engagement in financial toxicity.